Nearpod-Based Interactive Learning Media in Improving Learning Outcomes of Class V Elementary School Students - Yosefh Daniel Marcelino Banjarnahor; Daitin Tarigan (Indonesian Journal of Advanced Research, 2023)
This research is motivated by a learning process that rarely uses learning media in delivering material, so that students are less interested in following learning so that it affects student learning outcomes. The purpose of this study is to determine the richness, practicality, and effectiveness of using nearpod-based learning media. The type of research used is development research (Research and Development) which uses the ADDIE development model with 5 stages of research, namely Analyze, Design, Development, Implementation, and Evaluation. The subject of this study was a grade V student of SDN 101775 Sampali. The instruments used in data collection are teacher interviews, material and media validation questionnaires, education practitioner questionnaires, and tests. The results of the development of nearpod-based learning media on fractional material, showed that the results of material validation got a percentage of 93.75% with the category "Very Feasible" and the results of media validation got a percentage of 93.75% with the category "Very Feasible". Practicality validation by educational practitioners obtained a percentage of 92.30% with the category "Very Practical". Based on the effectiveness test of nearpod-based learning media developed, students' scores increased with the pre-test obtaining an average score of 56 and after the post-test increased to 88. From the research and data found, it shows that the development of nearpod-based learning media is very feasible and effective to be used in the learning continuity process.